Risk Assessment of Airbnb from Host’s Perspective: Evidence from a Mediterranean Island - Malazizi, Nahid (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
In the context of sharing economy, Airbnb has become a formidable mode of accommodation in the tourism industry worldwide, with a presence in over 34,000 cities in 191 countries. However, the risks associated with online bookings are significant dimensions of this e-market domain. This study assesses Airbnb hosts‘ perceived risks and investigates the effects of service, financial, safety and security, psychological and political risks on the host‘s satisfaction and intention to continue and recommend this business to potential hosts. A survey was administered to 221 Airbnb hosts located in Northern Cyprus. Structural equation modeling (SEM) was used to test the proposed conceptual model. The results revealed that host satisfaction is negatively influenced by financial and safety and security risks; continuance intention is negatively affected by financial, safety and security, and political risks; intention to recommend this business is negatively affected by political risk; and psychological risk increases satisfaction and intention to continue and recommend. By highlighting the theoretical and managerial implications, this study informs Airbnb management of the potential risks associated with this peer-to-peer (P2P) business in order to minimize the associated risks, enhance host satisfaction and the quality of their services, and encourage hosts to recommend Airbnb to their peers. Keywords: Airbnb, Risk, Host, Sharing Economy, Psychological Risk, Peer-to-Peer Business

ÖZ: Airbnb, paylaşım ekonomisi bağlamında, turizm endüstrisinde, dünya genelinde 191 ülkede ve 34.000'den fazla şehirde bulunması ile birlikte güçlü bir konaklama tarzı haline gelmiştir. Bununla beraber, internet rezervasyonundaki risk konusu e-pazar alanının önemli bir boyutudur. Bu araştırmanın amacı, Airbnb ev sahiplerinin algılarını ve çevrimiçi rezervasyon, çevrimiçi işlem, misafir ve ev sahibi etkileşimi sürecinde oluşabilecek ―risk‖ ile ilgili tutumlarını araştırmak ve anlamaktır. Ayrıca, bilgisayar ortamında yapılan Airbnb işlemlerinin algılanan risklerini değerlendirip, potansiyel risk türleri olan. hizmet, mali, güvenlik ve güvenlik, psikolojik ve politik risklerinin, etkilerini araştırmaktır. Ev sahibinin memnuniyetini ve bu işletmeyi ve internet ortamında yapılan bu işlemleri sürdürme ve potansiyel ev sahiplerine tavsiye etme niyetini anlamaktı. Araştırma, Kuzey Kıbrıs Türk Cumhuriyeti'ndeki bu işe aktif olarak katılan 221 Airbnb ev sahibi üzerinde yapılmıştır. Araştırma da, kümülatif olasılık teorisi (CPT) kullanılmıştır. Ayrıca, Veri analizi için Yapısal Eşitlik Modellemesi (SEM) yöntemi kullanılmıştır. Çalışmanın sonuçları Airbnb'nin yöneticilerine. içgörü olarak sunulmuştur. Ev sahiplerinin yaşayabileceği potansiyel riskleri keşfetmek, yaşanacak olan bu problemlerin üstesinden gelmeyi ve yönetmeyi kolaylaştıracaktır. Veri analizi, ev sahibi memnuniyetinin finansal, güvenlik ve güvenlik risklerinden olumsuz yönde etkilendiği görülmüştür. Bu işi tavsiye etme niyeti politik risklerden olumsuz yönde etkilenmektedir; ayrıca, psikolojik risk memnuniyetini, devam etme ve tavsiye etme niyetini artırır. Teorik ve yönetsel sonuçları vurgulayacak olursak, bu çalışma, ilgili risklerin en aza indirilmesi için çözümler bulmak Airbnb yönetiminin bu birebir (P2P) iş ile ilişkili potansiyel riskleri yönetmesini sağlamaktadır. Ev sahibi memnuniyetini ve hizmetlerinin kalitesinin arttırılması, Airbnb'yi yaşıtlarına önermek için ev sahiplerini teşvik etmektedir. Anahtar Kelimeler: Airbnb, Risk, Ev Sahibi, Paylaşım Ekonomisi, Finansal Risk, Güvenlik Risk, Psikolojik Risk, Birebir Iş(P2P).
Doctor of Philosophy in Tourism Management. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Tourism, 2018. Co-Supervisor: Asst. Prof. Dr. Hossein GT. Olya, Supervisor: Prof. Dr. Habib Alipour.
Keywords: Tourism; Vacation rentals--Management--Cyprus, North; Bed and breakfast accommodations--Vocational guidance--Airbnb (Firm); Hotel management--Vocational guidance; Rental housing--Management; Vacation rentals--Economic aspects; Tourism--Hospitality Industry--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Airbnb; Risk; Host; Sharing Economy; Psychological Risk; Peer-to-Peer Business